Meningkatkan Keaktifan Belajar Siswa Sekolah Dasar dengan Menggunakan Model Pembelajaran Cooperative Script - Anggraeni, Dian Nurvita (Prosiding University Research Colloquium, 2021)
The problem of second grade students at SD Negeri 2 Soropadan is the lack of student learning activity. The purpose of this study was to increase student activity using the cooperative script learning model. The research method used is Classroom Action Research which is divided into two cycles, each cycle consisting of four stages of activity, namely the stages of planning, action, observation, and subject reflection with research as many as ten class II SD Negeri 2 Soropadan, Pringsurat, Temanggung. . In cycle one, the data obtained by the average score of students as a whole is 76 (76%) which has exceeded the KKM, which is 74 with six students who have completed and four students have not completed. In cycle two there was an increase in the average total score of 7.5 to 83.5 (83.5%) with nine students who completed and one student who did not finish. So, it can be said that the cooperative learning model can increase student activity in participating in the learning process in class II SDN 2 Soropadan, Pringsurat, Temanggung.